A pituitary gene network linking vgll3 to regulators of sexual maturation in male Atlantic salmon - Ahi, Ehsan Pashay; Sinclair-Waters, Marion; Donner, Iikki; Primmer, Craig, R. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2023)
Animal experimentation followed European Union Directive 2010/63/EU under license ESAVI/42575/2019 granted by the Animal Experiment Board in Finland (ELLA). International audience Highlights: • c-jun and sf1 are potential upstream regulators of Atlantic salmon gonadotropins. • vgll3 affects the expression of c-jun and sf1, in the Atlantic salmon pituitary. • The vgll3 dependent regulations of c-jun and sf1are potentially achieved via distinct mechanisms. • A gene network linking vgll3 to c-jun acts through the canonical Hippo pathway. • The vgll3 dependent regulation of sf1 may be mediated by non-canonical Hippo pathway.Abstract: Age at maturity is a key life history trait and a significant contributor to life history strategy variation. The maturation process is influenced by genetic and environmental factors, but specific causes of variation in maturation timing remain elusive. In many species, the increase in the regulatory gonadotropin-releasing hormone 1 (GnRH1) marks the onset of puberty. Atlantic salmon, however, lacks the gnrh1 gene, suggesting gnrh3 and/or other regulatory factors are involved in the maturation process. Earlier research in Atlantic salmon has found a strong association between alternative alleles of vgll3 and maturation timing. Recently we reported strong induction of gonadotropin genes (fshb and lhb) in the pituitary of Atlantic salmon homozygous for the early maturation allele (E) of vgll3. The induction of gonadotropins was accompanied by increased expression of their direct upstream regulators, c-jun and sf1 (nr5a1b) but the regulatory connection between vgll3 and these regulators has never been investigated in any organism. In this study, we investigated the potential regulatory connection between vgll3 genotypes and these regulators through a stepwise approach of identifying a gene regulatory network (GRN) containing c-jun and sf1, and transcription factor motif enrichment analysis. We found a GRN containing c-jun with predicted upstream regulators, e2f1, egr1, foxj1 and klf4, ...